Oxide spin-orbitronics: New routes towards low-power electrical control of magnetization in oxide heterostructures - Vaz, Diogo Castro; Barthélémy, Agnès; Bibes, Manuel (Japanese Journal of Applied Physics, 2018)
The transition metal oxide family harbors various types of materials of interest for spintronics: half-metallic manganites are highly efficient spin injectors and detectors, yielding record values of tunnel magnetoresistance; multiferroic materials, and in particular BiFeO3, allow the electrical control of magnetization and spin excitations at room temperature; combined with ferromagnets, piezoelectric perovskites enable a controlled tuning of magnetic anisotropy, domain dynamics and even magnetic order. In this review, we argue that a new opportunity is emerging for oxides in spintronics with the rise of spin-orbit-driven phenomena such as the direct and inverse spin Hall and Rashba-Edelstein effects. After surveying the few results reported on inverse spin Hall measurements in oxide materials, we describe in depth the physics of SrTiO3-based interfaces and their usage for both spin-to-charge and charge-to-spin conversion. Finally, we give perspectives for a more thorough exploration of spin Hall effects in oxides and enhanced conversion ratios in both three- and two-dimensional structures.